IMPLEMENTASI PERDA PROVINSI BALI NOMOR 4 TAHUN 2019 TERHADAP PENANGANAN PERKARA ADAT DI DESA KUTUH - I Ketut Arka (Jurnal Inovasi Penelitian, 2023)
This research was conducted in Kutuh Village, South Kuta District, Badung Regency with the intention to know the problems or obstacles faced by Kertha Desa or village judges and how to solve customary cases that have occurred in Kutuh Traditional Village. In addition, this study also aims to know what cases have occurred and what sanctions should be given to the community who are considered to have committed violations, the design used in this study is qualitative descriptive that uses data sources obtained by interviewing community leaders and village Judges of Indigenous Village. This research uses analysis with the basis of theory as a guide to provide an overview of the background of research as a discussion of research results. Data analysis techniques used in this research is to analyse the data after data collection through observation, interview and documentation on the handling of customary cases resolved by Kerta Desa. After the data collected, then processing done that is adjusted to the needs of the analysis done. The initial process of data processing begins with towering through the editing process and then a descriptive qualitative analysis is carried out. Most cases or speeches handled by village judges in the in the past 10 years are divorce cases and livestock that enter the blooms of other citizens the settlement of the case is resolved simply by considering togetherness principle and in the effort in peace, besides Kerta Desa in handling the case does not have a written rule as a basis for determining the procedures and handling of cases governing of traditional village